Kajian Historis Model Ekonomi Melayu Pada Masyarakat Kesultanan Palembang - Muhammad Husni, Muhammad Husni (IQTISHADUNA, 2025)
The Palembang Darussalam Sultanate, established in the 17th century, was one of the most significant political and cultural entities in South Sumatra. As part of the Malay-Islamic civilization, its economic system reflected a synthesis of Islamic values and local practices. This study aims to explore the characteristics of the Malay economic model during the era of the sultanate as a historical inquiry that reflects the economic identity of the archipelago. It examines the economic dynamics of Malay society within the context of the Palembang Darussalam Sultanate. Using a historical approach and cultural analysis, this article investigates the structure, values, and mechanisms of traditional economic systems based on Islamic norms and local wisdom. The findings indicate that the Malay economic model within the Palembang Sultanate was built on a foundation of Islamic values and local customs that mutually reinforced one another. This system emphasized not only economic efficiency but also upheld ethics, distributive justice, and social solidarity. With a structure involving the active roles of the sultan, religious scholars, and indigenous communities, the sultanate successfully created an economic ecosystem oriented toward collective welfare. Economic activities such as trade, agriculture, waqf management, and zakat distribution were conducted in an integrated manner and reflected Sharia principles inseparable from local wisdom. Even in the face of colonial pressure and global change, this economic system demonstrated resilience and adaptability while maintaining its cultural and spiritual character. Therefore, the Palembang Sultanate’s economic model is not only relevant for historical understanding but also offers inspiration for designing more ethical, inclusive, and sustainable contemporary economic systems.